A Constant Struggle of Breastfeeding at Workplace: A Narrative Review - Elda Oncossya Panggabean; Ray Wagiu Basrowi (ILUNI MKK FKUI and PRODI MKK FKUI, 2024)
Breastfeeding has been shown and proved to offer numerous health benefits for infants and mothers. Despite this fact, studies have found that the level of exclusive breastfeeding continues to be low both in developed and developing countries. The issues with breastfeed and continue breastfeeding due to multiple factors, one of the biggest challenges is as a working mother. Working mothers face the challenge of balancing breastfeeding and paid work, thereby increasing the risk of early cessation of breastfeeding in general and exclusive breastfeeding. There are many studies to overcome these issues, however not many studies exposing the ethical issues, difficulties and opportunities while solving this matter. Such as moral work women undertake when engaging with breastfeeding, influenced by cultural and social norms that makes it harder for breastfeeding mother.